Reconsidering Self-Portraits by Women Surrealists: A Case Study of Claude Cahun and Frida Kahlo - Josten, Jennifer (Atlantis)

(untitled) (Mount Saint Vincent University, 2006)
Both Claude Cahun and Frida Kahlo were affiliated with the Surrealist movement in the 1930s for political and professional ends. In their respective bodies of self-portraiture, they mirrored or doubled their own images and stretched the boundaries of gender and sexual representation in order to challenge heteronormative conceptions of identity.